Identification of tumor stem-like cells in a mouse myeloma cell line - Dou, J; Li, Y; Zhao, F; Hu, W; Wen, P; Tang, Q; Chu, L; Wang, Y; Cao, M; Jiang, C; Gu, N (Cellular and Molecular Biology, 2009)
We used colony formation assay in the soft agar media or the serum-free media, the methods of identifying BrdU-label-retaining cells and the SP cells as well as the tumorigenicity test in BALB/c mice, respectively, to analyze tumor stem like cells in the SP2/0 cell line. The results showed that a few SP2/0 cells were capable of forming colonies in the soft agar media, contained BrdU-label-immortal strand in the SP2/0 cell line. The SP2/0 cells in the serum-free media gained higher tumorigenicity in the BALB/c mice than the SP2/0 cells cultivated in the complete media did. Overall, only a few of the SP2/0 cells were found to possess the characteristics of tumor stem-like cells, such as high proliferative potency, more self-renewal and stronger tumorigenesis, or greater similarity to the tumor stem cells (TSCs) traits. The biology of tumor stem-like cells contributes to the identification of molecular targets important for future tumor therapy.